Pengaturan Kecepatan Motor Menggunakan Metode Fuzzy Pada Roll Banner - Abubakar, Aldillah; Wardana, Angga Candra; Rasmana, Susyanto Tri; Martadinata, Yuwono (Journal JCONES, 2012)
Dc motors are widely used in industry as a driver mechanic, because it has the ease of control, ie by setting anchor motor current which is proportional to acceleration or torque. Dc motors are usually operated for a constant speed, but when the load changes, it changes speed. Because it must be a constant speed by reducing the amount of error that occurs in accordance with the desired system. To get the best performance for the stability of the system response in accordance with the desired, then the fuzzy controller used to regulate the speed of dc motor.